The Clinical Features of Macular Pucker Formation after Pars Plana Vitrectomy for Primary Rhegmatogenous Retinal Detachment Repair - Heo, Moon Soo; Kim, Hyun Woong; Lee, Joo Eun; Lee, Sang Joon; Yun, Il Han (Korean journal of ophthalmology, 2012)
To investigate the incidence and predisposing factors of macular pucker formation after pars plana vitrectomy in patients who developed primary rhegmatogenous retinal detachment. We retrospectively reviewed a consecutive series of 284 eyes in 284 patients who underwent primary retinal detachment repair by pars plana vitrectomy alone between January 1, 2009 and December 31, 2010. Patients with a history of retinal surgery or another visually significant ocular problem were excluded. Postoperatively, of the 264 eyes that completed at least six months of follow-up, 16 (6.1%) eyes developed obvious macular pucker at clinical examination. Of these 16 eyes, ten (70.0%) underwent repeat vitrectomy with membrane peeling for macular pucker removal during the follow-up period. The mean time from primary vitrectomy for the retinal reattachment to the secondary vitrectomy with membrane peeling for macular pucker was 7.9 months. The mean improvement in vision after membrane peeling surgery was 0.37 (logarithm of the minimum angle of resolution). Using an independent t-test, chi-square test, and Mann-Whitney U-test, we found that the number or size of retinal break and vitreous hemorrhage could be significant risk factors of macular pucker. In our study, 6.1% of eyes which underwent pars plana vitrectomy alone for primary retinal detachment developed a postoperative macular epiretinal membrane. Multiple or large retinal breaks and postoperative vitreous hemorrhage were related to macular pucker formation. Overall, the 70.0% of eyes which underwent secondary vitrectomy with membrane peeling for removal of macular pucker showed a favorable visual outcome.